Pengaruh Perkuliahan Fisika Berbasis Proyek Terhadap Keterampilan Generik Sains Mahasiswa - Khoiri, Nur (Universitas PGRI Semarang, 2023)
This study aims to determine the effectiveness of project-based lecture programs to develop students' generic science skills in making teaching aids in physics learning. The method used in this research is quasi experiment. The sample of this research was college students consisting of 30 students, and formed into 10 groups. The required data requirements are determined by appropriate assessment techniques, namely observation, practice tests, and group assignments. The results showed that all aspects of the assessment of teaching aids that had been made by students were in a very good category, in addition to that the average score of the students' generic science skills was also good because students designed their own practical activity guides, so that students had constructed knowledge about the aspects of generic science skills that were appear at activity stages. Lecture activities that reflect science attitudes and behavior have had an impact on improving students' generic science skills.Keywords: physics learning, project based learning, generic science skills